Σχεδιασμός συστημάτων μέτρησης και έλεγχου τάσης ινών Κevlar σε μηχανή μορφοποίησης με εμβάπτιση - Προκοπίου, Παναγιώτης; Θεοδώρου, Ελένη (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
Currently most pultrusion machines are not endowed with an economical method via which the tension of the wetted fibers just prior to their ingress into the forming die can be measured and controlled. A little tension is necessary if the fibers are to enter the die property aligned, but if this tension is too high it will generate undesirable residual stresses in the consolidated product. Equally important is the fact that the tension in all the fibers entering the die must be approximately uniform in order to avoid warping or other undesirable deformation. The main objective of this project was to design a simple and economical system that can monitor and control the fiber tension just prior to the die entrance. Another objective was to enrich our knowledge on general composite materials.
Keywords: Pultrusion Machines; Tension Of The Wetted Fibers; Mηχανές Mορφοποίησης με Eμβάπτιση; Tάση Eμβαπτισμένων Iνών